Odpowiedzi

2010-02-25T21:57:08+01:00
23-3*[-2,4+(-14,7):4 1/5=23-3*(-2,4-3,5)=23-17,7=40,7

10-2*[(-1,6)+(-19,5):(-2 1/2)=10-2*(-1,6 - 7,8)= 10- 18,8= -8,8

[2/3*0,125+(-4,5)]:[-3 2/3+(-14)]= -4,417 : -17i2/3= -0,25
2010-02-25T22:43:15+01:00
23-3*[-2,4+(-14,7):4 1/5= brak d zamkniecia nawiasu kwadarowego ]
= 23 -3*[ -2,4 +(-147/10):(21/5)=
= 23 -3 *[ -2,4+ (-147/10)*(5/21)=
= 23 -3 *[ -24/10 - 7/2 =
= 23 -3 *[ -24/10 - 35/10 =
= 23 -3*[ -59/10]=
= 23 + 177/10=
= 23 + 17,7=
=40,7

10-2*[(-1,6)+(-19,5):(-2 1/2)=
=10 - 2*[(-1,6 )+ (-195/10) : (- 5/2)=
= 10 - 2*[ (-1,6) + (-195/10) *(-2/5)=
= 10 -2*[ (-1,6) + 78/10]=
= 10 - 2*[ -1,6 + 7,8]=
= 10 -2*1,6 =
= 10 - 3,2=
= 8,8

[2/3*0,125+(-4,5)]:[-3 2/3+(-14)=
=[ 2/3* 1/8 + (- 45/10)] : [ (-11/3 - 42/3]=
= [ 1/12 - 9/2] : [ -53/3]=
= [ 1/12 - 54/12]*(-3/53) =
= [ -53/12]*(-3/53)=
= 1/4